If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xb + -1bx(-3) + 3x(-1b) = 0 Reorder the terms for easier multiplication: 3bx + -1 * -3bx + 3x(-1b) = 0 Multiply -1 * -3 3bx + 3bx + 3x(-1b) = 0 Remove parenthesis around (-1b) 3bx + 3bx + 3x * -1b = 0 Reorder the terms for easier multiplication: 3bx + 3bx + 3 * -1x * b = 0 Multiply 3 * -1 3bx + 3bx + -3x * b = 0 Multiply x * b 3bx + 3bx + -3bx = 0 Combine like terms: 3bx + 3bx = 6bx 6bx + -3bx = 0 Combine like terms: 6bx + -3bx = 3bx 3bx = 0 Solving 3bx = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '3'. bx = 0 Simplifying bx = 0 The solution to this equation could not be determined.
| 1/3k-1=4/6 | | In*(x-6)+In*(x-4)=In*15 | | 6x-9-4x=13 | | (4y+7)(4-y)=0 | | q(z)=pz+b | | ln*(x-5)+ln*(x-8)=ln*28 | | x-1/5=3-(x-9)/2 | | (150-80/1-x)2x=0 | | 40-(5)x=8+x | | (5-3x)2x=0 | | (4g-2)*(4g-2)=4 | | 3(2m-8)-4m=20 | | 2sinx=5+cosx | | 4.5=4t^2 | | 7x^2+7x=9 | | cos7x=cosx/3 | | 11-4+(-1)*5= | | 9t+18-3t-15= | | y=2x^4-4x^2+15 | | 2(2x-1)-3(x+3)=x+1 | | 7y+8y-3x-4x= | | 2x-25+7x-75=7x-20 | | 7x-x^3=6 | | 9x+3y-6x+2y= | | 4w+10=-3(w-8) | | 25x+7x-4x-6x= | | Sinx=-.72 | | 2(d+6)=-2d-12 | | X+40+y=180 | | 2x+33=7x+3 | | 0.84xa=1 | | X^2-(1+3i)x-2+2i=0 |